1997
DOI: 10.1542/peds.99.6.e6
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and Physicians’ Views on Antibiotics

Abstract: ABSTRACT. Objective. To describe parents' opinions and concerns about antibiotics and to contrast these opinions with those of pediatricians.Design. Parents were surveyed using an intervieweradministered questionnaire and pediatricians were mailed a self-administered questionnaire.Results. Parents from two private practices (N ‫؍‬ 300) were largely white (84%) and had completed college (81%). The parents from a community health center (N ‫؍‬ 100) were mostly black (80%) and had not completed college (91%). Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 21 publications
1
94
0
2
Order By: Relevance
“…Lindberg and colleagues found that the 13 patients they interviewed related resistance to the bacterium, which is not so surprising given that the term itself declares the Staphylococcus resistant, and that this organism is also commonly known as a 'super-bug'. 37 Nevertheless, most surveys about the public perception of antibiotic resistance have been naïve to the possibility of multiple interpretations of the term antibiotic resistance', [11][12][13][14][15] and did not give respondents the opportunity to elaborate on the issue. [13][14][15] Respondents to those surveys may not have interpreted antibiotic resistance as intended by the researchers.…”
Section: Results In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Lindberg and colleagues found that the 13 patients they interviewed related resistance to the bacterium, which is not so surprising given that the term itself declares the Staphylococcus resistant, and that this organism is also commonly known as a 'super-bug'. 37 Nevertheless, most surveys about the public perception of antibiotic resistance have been naïve to the possibility of multiple interpretations of the term antibiotic resistance', [11][12][13][14][15] and did not give respondents the opportunity to elaborate on the issue. [13][14][15] Respondents to those surveys may not have interpreted antibiotic resistance as intended by the researchers.…”
Section: Results In Contextmentioning
confidence: 99%
“…11,12 For example, surveys examining patients' attitudes have used fixed questions with little or no opportunity for follow-up of patients' views or understanding. [13][14][15][16] Few studies have explored patients' understanding of antibiotic resistance as a term used in healthcare discourse. Although two recent qualitative studies have explored patient and public attitudes towards antibiotic resistance, they were limited to the United Kingdom, and the wider implications were not considered in depth.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients seek care for acute respiratory illnesses, such as upper respiratory infections, with the explicit intent of getting a prescription for antibiotics, [36][37][38] and clinicians appear to prescribe antibiotics in response to these expectations. 38,39 A final possible explanation for the high antibiotic prescription rate for acute bronchitis is that clinicians believe antibiotics benefit acute bronchitis, despite the evidence in the medical literature. When we reviewed the management of acute bronchitis in several popular general medicine and family medicine textbooks, we found a wide range of treatment recommendations that both promoted 40,41 and denounced 42,43 antibiotic use for acute bronchitis.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that parent pressure is commonly cited by physicians as a reason for prescribing (Barden, Dowell, Schwartz, & Lackey, 1998;Palmer & Bauchner, 1997;Schwartz, 1999;Schwartz, Freij, Ziai, & Sheridan, 1997). Several communication practices used by parents appear to be what actually constitutes ''pressure'' (Stivers, 2002a, b, in press;.…”
mentioning
confidence: 99%